2009
DOI: 10.1002/chem.200900249
|View full text |Cite
|
Sign up to set email alerts
|

On the Electronic Impact of Abnormal C4‐Bonding in N‐Heterocyclic Carbene Complexes

Abstract: Versammlungsverbot für Tau‐Proteine: Die pathologische Aggregation von Tau‐Proteinen hängt eng mit dem Fortschreiten der Alzheimer‐Krankheit zusammen. Von Rhodanin abgeleitete Inhibitoren (z. B. 1) hemmen die Tau‐Aggregation in einem Zellmodell reversibel und in nanomolaren Konzentrationen (siehe SEM‐Bilder).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 119 publications
2
69
0
4
Order By: Relevance
“…38 Structural disparity between the two complexes arises predominantly because of the different Pd-Cl bond lengths, as a consequence of the stronger trans influence of the C4-bound carbene ligand. However, the http://doc.rero.ch 6 reactivity of the complexes varies considerably.…”
Section: C-h Bond Activation Of C2-substituted Imidazolium Saltsmentioning
confidence: 99%
“…38 Structural disparity between the two complexes arises predominantly because of the different Pd-Cl bond lengths, as a consequence of the stronger trans influence of the C4-bound carbene ligand. However, the http://doc.rero.ch 6 reactivity of the complexes varies considerably.…”
Section: C-h Bond Activation Of C2-substituted Imidazolium Saltsmentioning
confidence: 99%
“…A reactivity sequence that may model this catalyst activation step was recently disclosed by reacting the palladium complexes with chlorine rather than with hydrogen. [14] Exposure of complexes similar to 4 to Cl 2 afforded instantaneously the doubly chlorinated imidazolium salt with [PdCl 4 ] 2À as counterion. Substituting chlorine in this process with hydrogen would provide the protonated imidazolium salt, as observed in substoichiometric catalytic runs, and [PdH 4 ] 2À as precursor for palladium nanoparticles.…”
Section: Mechanistic Investigationsmentioning
confidence: 99%
“…[10,13] This enhanced donor ability provides access to new reactivity pathways. Specifically, the high electron density imparted to the metal center is surmised to facilitate oxidative addition reactions, [14] which are a key step in the metal-mediated activation of H 2 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Only recently it has been shown that an abnormal binding mode via the C4 (or C5) position of imidazolylidenes yields extraordinary electron rich metal centers. [6][7][8][9][10][11][12][13][14][15][16][17] These discoveries led to a considerably increased interest in "non-classical" NHCs, i.e. carbenes that are not stabilized by two adjacent heteroatoms.…”
Section: Introductionmentioning
confidence: 99%